The nexus between financial development and trade performance: Empirical evidence from India in the presence of endogenous structural breaks. Issue 2 (4th December 2019) - Arora, Puneet Kumar; Mukherjee, Jaydeep
Abstract : Purpose: This study aims to empirically examine the relationship between financial development and trade performance for the Indian economy through a time-series analysis with annual data over the period 1980-2016. Design/methodology/approach: The study uses new econometrics techniques such as unit root tests in the presence of endogenous structural breaks and autoregressive-distributed lag bounds test for the analysis. Findings: Empirical results reveal that the level of financial development has a significant positive impact on the exports, imports and trade balance of manufactured goods for the Indian economy. Practical implications: The findings suggest that the positive effect of financial development on trade performance is a potential mechanism through which the former may affect overall income and growth rates. It also implies that standalone trade liberalisation policies are insufficient to increase Indian exports. Indian policymakers should, therefore, consider the implications of the next set of financial sector reforms on the country's trade flows, besides their positive impact on the economic performance. The findings are particularly relevant in the present scenario when the export growth is decelerating and there is a marked slowdown in private credit flows because of the problem of non-performing assets. Originality/value: This study is the first of its kind which provides a holistic analysis of the relationship between financial development and trade performance for the Indian economy and also investigates the direction of causality between financial development and international trade by considering the possible presence of multiple endogenous structural breaks in the data. Moreover, in contrast to the available literature, the present study focuses on net exports as a key indicator of trade performance rather than trade openness.